Anmeldelser - Struck, Michael (Danish Yearbook of Musicology, 2008)
Review of: J.P.E. Hartmann, Liden Kirsten / Little Kirsten / Klein Karin, op. 44. Opera in two acts. Text by Hans Christian Andersen, ed. Inger Sørensen and Niels Krabbe. The Hartmann Edition, IV, 1; Copenhagen: The Royal Library, 2005. J.P.E. Hartmann, Vølvens Spaadom / The Prophecy of the Sibyl / Wahrspuch der Wölwe, op. 71. Digt af den ældre Edda / Poem from the Poetic Edda / Lied der Älteren Edda, adapted by Fr. Winkel Horn, ed. Niels Krabbe. The Hartmann Edition, V, 1; Copenhagen: The Royal Library, 2006